Sistem Informasi Bisnis Digital Bunga di Kota Tomohon: Flower Digital Business Information System in Tomohon City - Treysi Maria Valleyn Pusung Treysi (Jurnal Teknik Informatika, 2024)
Tomohon City is known as the "City of Flowers" due to its abundant flower production. Therefore, many of its residents are engaged in farming and selling flowers for their livelihoods. The wide variety of flowers in the city attracts people from outside Tomohon who come to search for flowers in the city. However, often,many people arrive, but the desired type of flower is unavailable because the sales process is still manual. Furthermore, manual transactions often pose challenges. This research aims to develop an information system based on an Android application that enables customers to purchase and explore various options of fresh flowers from local flower vendors in Tomohon City.The development method of this application involves analyzing customer requirements, designing an intuitive user interface, and developing an Android-based application. This application allows users to search, view descriptions, and order various types of flowers, as well as provides information on prices and availability. Additionally, customers can select a suitable delivery address and pay for their orders online through provided payment methods.The research results show that this application successfully connects consumers with local flower vendors, facilitates online transactions, and enhances the accessibility of fresh flowers in Tomohon City. The research is expected to improve customer service and assist local flower vendors in competing more effectively in an increasingly competitive market.